2000
DOI: 10.1348/014466500163077
|View full text |Cite
|
Sign up to set email alerts
|

The timing, triggers and qualities of recovered memories in therapy

Abstract: On the basis of current understanding of memory processes, several mechanisms may be needed to explain all the data, including disruptions to the encoding and retrieval of traumatic events and errors in the attribution of the source of specific memories. It will be important to confirm these findings by interviewing clients themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 49 publications
2
9
0
1
Order By: Relevance
“…To determine how accessible these memories were during the period of forgetting, participants were asked whether they had simply avoided thinking about the abuse, had a vague sense that something negative had happened but were unaware of what it was, or had been totally unaware that any sexual abuse had occurred. In line with past research (Andrews et al, 1999(Andrews et al, , 2000 only those who reported a vague sense (N ¼ 20) or that they had been totally unaware of all or a significant part of the abuse (N ¼ 22) after age 5 were classified as having forgotten the abuse. An attempt to validate the abuse memories of the 'forgetting' group was made by asking all the CSA women if they had ever come across or tried to obtain verification for their memories of abuse.…”
Section: Memory For Childhood Sexual Abusesupporting
confidence: 61%
“…To determine how accessible these memories were during the period of forgetting, participants were asked whether they had simply avoided thinking about the abuse, had a vague sense that something negative had happened but were unaware of what it was, or had been totally unaware that any sexual abuse had occurred. In line with past research (Andrews et al, 1999(Andrews et al, , 2000 only those who reported a vague sense (N ¼ 20) or that they had been totally unaware of all or a significant part of the abuse (N ¼ 22) after age 5 were classified as having forgotten the abuse. An attempt to validate the abuse memories of the 'forgetting' group was made by asking all the CSA women if they had ever come across or tried to obtain verification for their memories of abuse.…”
Section: Memory For Childhood Sexual Abusesupporting
confidence: 61%
“…) Trauma at different stages of life (early childhood abuse as well as trauma in later life [e.g., due to combat]) has been thought to influence hippocampal volume. Several clinical studies have also reported alterations in learning and memory in patients with PTSD, which are consistent with both deficits in encoding on explicit memory tasks and deficits in retrieval, as well as enhanced encoding or retrieval for specific trauma-related material (Andrews et al 2000;Buckley et al 2000;Gilbertson et al 2001;Pitman 1989;Roca and Freeman 2001;Vasterling et al 1998;Wolfe and Schlesinger 1997). The majority of these studies found deficits in verbal memory, with a relative absence of deficits in tasks of attention or visuospatial memory.…”
Section: Introductionmentioning
confidence: 64%
“…As with PTSD, mechanisms have been proposed whereby such forgetting and subsequent (possibly erroneous) retrieval might occur (Schacter 1996), particularly in relation to certain cues or triggers (Andrews 2000).…”
Section: Childhood Sexual Abusementioning
confidence: 99%